An Analysis of Directive Illocutionary Acts Found in DC League of Super-Pets Movie - Malini, Ni Made Jilina Cantika; Ariyaningsih, Ni Nyoman Deni (STKIP AGAMA HINDU SINGARAJA, 2024)
This study analyzed one of the illocutionary speech acts namely directives act. Directive illocutionary acts are used by the speaker to get the hearer to do an action. This study discusses the types of directive illocutionary acts as well as the function of directive illocutionary acts. The researchers applied two theories in analyzing the study. The first theory was proposed by Kreidler (1998) used to analyze the types of directives illocutionary acts. The second theory was proposed by Leech (1983) used to analyze the function of directive illocutionary acts. The researchers used the documentation method to collect the data. This data was analyzed with qualitative method. Qualitative methods were used to analyze the data descriptively. In presenting the data, the researcher used formal and informal methods. In this study, there are 64 data of directive illocutionary acts classified into 41 data or 64,1% of commands, 14 data or 21,8% of requests, and the last data is 9 or 14,1% of suggests. There are four types of functions found in command types, namely competitive, convivial, collaborative, and conflictive. Meanwhile, in requests and suggest types, there are only two functions found namely competitive and convivial.